G-CSF Infusion for Stem Cell Mobilization Transiently Increases Serum Cell-Free DNA and Protease Concentrations - Stoikou, Maria; van Breda, Shane V.; Schäfer, Günther; Vokalova, Lenka; Giaglis, Stavros; Plattner, Alexandra; Infanti, Laura; Holbro, Andreas; Hahn, Sinuhe; Rossi, Simona W.; Buser, Andreas (Frontiers in Medicine, 2020)
G-CSF for stem cell mobilisation increases circulating levels of myeloid cells at different stages of maturation. Polymorphonuclear cells (PMNs) are also mobilised in high numbers. It was previously reported that G-CSF primes PMNs towards the release of neutrophils extracellular traps (NETs). Since NETs are often involved in thrombotic events, we hypothesised that high G-CSF blood concentrations could enhance PMN priming towards NET formation in healthy hematopoietic stem cell donors, predisposing them to thrombotic events. However, we found that G-CSF does not prime PMNs toward NETs formation, but increases the serum concentration of cell-free DNA, proteases like neutrophils elastase and myeloperoxidase, and reactive oxygen species. This could possibly create an environment disposed to induce thrombotic events in the presence of additional predisposing factors.